Towards a systematic review of the translating skills of the legal translator - Podleskis , Jean-Norbert (2024)
Legal translation is an active and growing field of expertise, for which it is necessary to prepare translation students adequately. It is therefore important to determine the competencies associated with legal translation. In this review, we have tried to gather some of the most significant contributions in this regard. The models developed by Dorothy Cao, Fernando Prieto, Beata Piecychna, Ewa Kościałkowska-Okońska, Federia Scarpa and Daniele Orlando, and Guadalupe Soriano are thus reviewed. The contribution of authors highlighting the importance of some particular competences is also collected.